Executive Summary of Educational Content from EMS Agenda 2050. (3rd September 2019) - Leggio, William J.; Neeley King, Kyra; Gienapp, Andy; Bergsten, Derek; Yu, YiDing; Gausche-Hill, Marianne
Abstract: EMS Agenda 2050 follows the original EMS Agenda for the Future and EMS Education Agenda for the Future. These visionary documents discussed and described learning content, requirements, and design of EMS education. This article written by members of the EMS Agenda 2050 Technical Expert Panel highlights the content in the preceding agendas for the future and content from EMS Agenda 2050 in an effort to provide a summarized guide for new and existing EMS education curriculums.